Genetic tests reveal extra‐pair paternity among Gentoo penguins (Pyogoscelis papua ellsworthii) at Loveland Living Planet Aquarium: Implications for ex situ colony management. Issue 4 (11th July 2018) - Lee, Lauren; Tirrell, Nathan; Burrell, Christian; Chambers, Scott; Vogel, Steve; Domyan, Eric T.
Abstract : Maintenance of ex situ populations for species conservation is a collaborative effort involving multiple agencies, institutions, and individuals around the world. Gentoo penguins ( Pyogoscelis papua ) are one species involved in such a conservation effort, and a Species Survival Plan (SSP) has been put in place by the Association of Zoos and Aquariums (AZA) to foster their long‐term sustainability. As a part of their SSP, a Breeding and Transfer Plan has been created to support interagency exchanges of specimens. These transfers are vital to the demographic health and stability of ex situ populations, as well as the maintenance of genetic diversity. In populations such as the Gentoo, where social monogamy exists, paternal inferences of offspring are usually made through observation of birds' social behavior. However, social monogamy does not guarantee reproductive monogamy. In this study, we utilize Illumina high‐throughput DNA sequencing to genetically test the postulated paternity of Gentoo penguins born at Loveland Living Planet Aquarium (LLPA) in Draper, UT. While our data support the majority of the postulated relationships, we did identify two offspring that were the result of extra‐pair paternity (EPP). The results of this research highlight the importance of genetic tests to validate pedigrees used in SSPs, to provide more‐accurate data for the support of species conservation.